Meningkatkan Hasil Belajar Siswa SMP Negeri 2 Gunungsari Melalui Penerapan Model Pembelajaran Guided Discovery Learning - Inna, Marcelya; Safnowandi, Safnowandi; Armiani, Sucika (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Education is an effort made to achieve a certain goal. Through these efforts, it is hoped that students can increase their knowledge and explore the potential they have, so that it can be useful for themselves and others. The aim of this research is to determine student learning outcomes through the application of the guided discovery learning model. The type of research used is qualitative descriptive research. This research design is a one shot case study. The population in this study were class VII students of SMP Negeri 2 Gunungsari. The sample used in this research was class VIIA and VII B of SMP Negeri 2 Gunungsari. The instrument used in this research is a learning outcomes test sheet. In this research, the type of test used was a multiple choice form with 4 answer choices. One correct answer and three wrong answers, the score for each question is one if correct and zero if incorrect. The data analysis techniques used are individual and classical completeness and indicator completeness. Based on the research data, it can be stated that of the 10 indicators tested in the pretest, all indicators had an average percentage of completeness of 13.4%, while in the posttest all indicators had an average percentage of completeness of 64.5%. Thus it can be concluded that the application of the Guided Discovery Learning (GDL) model can improve student learning outcomes. This is because this learning can invite students to play an active role, students are able to interact, collaborate with their group friends, and involve the students' initial abilities.